1994
DOI: 10.1002/ardp.19943270414
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antifungal Activity of Some 2‐Aryl‐3‐substituted 4‐Thiazolidinones. Synthese und antimykotische Aktivität einiger 2‐Aryl‐3‐substituierter 4‐Thiazolidinone

Abstract: In continuation of our studies on the synthesis and biological activity of 4-thiazolidinone~'.~), we here report the synthesis of some hydrazones and 4-thiazolidinones carrying an imidazo[ 1.2-alpyridine moiety at the Natom, prepared with the objective of screening their antifungal activities. Table 1 The IR-spectra of 2a-h and 3a-h show CO bands at 1640-1580 cm-I (COW-N). A new strong band at 1710 cm-' in the spectra of 3a-h provides f i r m support for ring closure. After the reaction with mercaptoacetic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Diverse biological activities such as bactericidal, 1,2 fungicidal, 3,4 insecticidal, 5,6 anticonvulsant, 7-9 tuberculostatic, 10,11 herbicidal, 12,13 antiviral, 14,15 and antiprotozoal 16 have been found with thiazolidinone derivatives. The diversity of biological and physiological activities of organic sulfur heterocycles may be attributed to the presence of the N C S fragment, which is characteristic of thiazoles, thiazolines, and thiazolidines.…”
Section: Introductionmentioning
confidence: 98%
“…Diverse biological activities such as bactericidal, 1,2 fungicidal, 3,4 insecticidal, 5,6 anticonvulsant, 7-9 tuberculostatic, 10,11 herbicidal, 12,13 antiviral, 14,15 and antiprotozoal 16 have been found with thiazolidinone derivatives. The diversity of biological and physiological activities of organic sulfur heterocycles may be attributed to the presence of the N C S fragment, which is characteristic of thiazoles, thiazolines, and thiazolidines.…”
Section: Introductionmentioning
confidence: 98%
“…A new strong band at 1764-1713 cm -1 in the spectra of 3a-j provided firm support for ring closure (Cesur et al, 1994). In the 1 H-NMR spectra of compounds 3a-j, NH protons appeared as a singlet (1H) at 11.10-9.91 ppm, the CH-CH 3 protons appeared as a quartet (1H) at 4.68-4.35 ppm and CH-CH 3 protons appeared as a doublet (3H) at 1.72-1.48 ppm which proved the closure of 4-thiazolidinone ring (Farghaly et al, 1990).…”
Section: Chemistrymentioning
confidence: 97%
“…1,2,3–Triazole and thiazolone scaffolds have shown various biological activities including; antitumors, [ 1,2 ] anti‐HIV, [ 3 ] anti‐allergy, [ 4 ] antifungal, [ 5–7 ] anti‐infection, [ 8,9 ] anticancer, [ 10 ] antiviral, [ 11–13 ] and antimicrobial properties. [ 14–22 ] Furthermore, the regioselectivity of cycloadducts is crucial [ 23–26 ] and it has been found that some 1,2,3‐triazole and thiazolone derivatives exhibited antityrosinase activity.…”
Section: Introductionmentioning
confidence: 99%